Development Of Web Application Based On Crowdsourcing For Car Rental Management By Using Scrum Methodology (customer Side) - Ghoziyah Haitan Rachman; Soni Fajar Surya Gumilang; Taufik Nur Adi (eProceedings of Engineering, 2015)
Abstract—Too much information about various car rental services provider is spreading out on the Internet within many different websites. This matter makes almost half of the people find difficulty to get the car rental information directly, because they will hardly filter information one by one according to their needs with the limited time they have. Therefore, they rely more on information that comes from mouth to mouth or suggestions from nearest people. The research aims to develop a web application based on crowdsourcing for car rental management focused on customer side specifically in order to store the rented cars information from various rentals become centralized. Then, by this application, renters do not need to open each of the car rental websites when they want to rent multiple cars. For application development, it will use Scrum methodology made in six sprints by involving analysis, designing, coding, and integration. Web application itself is built by using concept of Model-View-Controller (MVC) which utilizes PHP programming language within Laravel framework and MySQL database. The result of research is crowdsourcing- based website application to help customers not only be easy to search rented cars, but also easy to book multiple cars from various rentals until confirm their payment. Moreover, they can share information electronically through social media faster than mouth to mouth. The research application is additionally able to help many rentals for promoting their cars and increase the satisfactory services to renters. Index Terms—Car Rental Management, Web Application, Crowdsourcing, Scrum